1998
DOI: 10.1007/pl00008983
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oxygen concentration in liquid medium on elemental sulphur oxidation by Thiobacillus thiooxidans

Abstract: Rate of elemental sulphur biooxidation byThiobacillus thiooxidans bacteria in continuous culture with nutrient circulation was determined for oxygen concentration in liquid in the range 1±17 mg/dm 3 for temperature range 19±40°C, pH from 1.5 to 4.5 and for CO 2 concentration above 110 mg/dm 3 . Equation describing the in¯uence of above mentioned parameters on the rate of sulphur oxidation was presented. List of symbolsC AB alive bacteria protein concentration, [lg/ml] C B total bacteria protein concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The dissolved oxygen concentration directly influences the growth of At. thiooxidans and its capacity to oxidize S 0 (Jaworska and Urbanek, 1998). Thus, a lack of dissolved oxygen also may have negative effects on biofilm growth and structures of Acidianus sp.…”
Section: Resultsmentioning
confidence: 99%
“…The dissolved oxygen concentration directly influences the growth of At. thiooxidans and its capacity to oxidize S 0 (Jaworska and Urbanek, 1998). Thus, a lack of dissolved oxygen also may have negative effects on biofilm growth and structures of Acidianus sp.…”
Section: Resultsmentioning
confidence: 99%
“…it grows well at pH 2 as shown in Table 2.6). Jaworska and Urbanek (1998) reported that the optimum temperature for Acidithiobacillus thiooxidans was 33 o C. The shape of Acidithiobacillus thiooxidans is short rod, 0.5 by 1~2 μm, occurring singly, in pairs or in short chains. Colonies on thiosulfate agar are minute (<1.0 mm), transparent or whitish or yellow (Bergey and Holt, 1994), and usually appear after 2~3 days since inoculation.…”
Section: Microorganisms For H 2 S Removalmentioning
confidence: 99%